Comparative evaluation of coronally advanced flap using amniotic membrane and platelet-rich fibrin membrane in gingival recession: An 18-month clinical study - Mohd Rehan; Manish Khatri; Mansi Bansal; Komal Puri; Ashish Kumar (Wolters Kluwer Medknow Publications, 2018)
Background: An amnion membrane is a placenta-derived tissue that consists of numerous growth factors, proteins, and stem cell reserves which help in accelerated wound healing and regeneration. Platelet-rich fibrin (PRF) also releases growth factors after activation from the platelets and gets trapped within fibrin matrix which has been shown to stimulate the mitogenic response in the periosteum for bone repair and regeneration during normal wound healing. This preliminary, controlled, randomized clinical trial with an 18-month follow-up was aimed to evaluate the effectiveness of coronally advanced flap (CAF) with either PRF membrane or bioresorbable amniotic membrane (AM) in treatment of localized gingival recession defects. Materials and Methods: Sixteen healthy adult patients presenting with Miller Class I recession defects were treated surgically with CAF along with AM (Group I) or PRF (Group II) for coverage of the recession defects. For all patients, plaque index, gingival index, bleeding on probing, clinical attachment level, depth of recession, width of recession, width of attached gingiva, and gingival thickness were evaluated at 6 months and 18 months postoperatively. Statistical analysis was done using paired t-test, repeated measure analysis of variance test, Bonferroni test for intragroup comparison and unpaired t-test for intergroup comparison. Results: The results showed statistically nonsignificant (P < 0.01) difference in all clinical parameters at the 6- and 18-month follow-ups in both groups. Gingival recession in both PRF and amnion group when evaluated individually, significantly reduced from baseline to 6 months (P = 0.000) and from baseline to 18 months (P = 0.000). However, the mean value from 6 months to 18 months was statistically nonsignificant. Conclusion: The present study demonstrated that both CAF + PRF and CAF + AM are equally effective in providing clinically significant outcomes with respect to root coverage with AM showing the better percentage of root coverage as compared to PRF.